Perbandingan Efektivitas Infusa Daun Jambu Biji Merah (Psidium Guajaval) Dengan Temephos Terhadap Kematian Larva Nyamuk Aedes Aegypti - Bitha Miranda Nasution; Desi Isnayanti (Universitas Muhammadiyah Sumatera Utara, 2020)
Introduction: Aedes aegypti mosquito is the main vector of dengue virus. Aedes aegypti mosquito control efforts one of them by breaking the life of mosquito chain in larval stage that can be eradicated by chemical means that is using temephos, but the use of chemical larvasida can harm society like environmental pollution. The alternative to reducing the loss is by using natural ingredients is red guava leaf infusa ( Psidium guajava L) containing chemicals that can kill the larvae. Methods: This study uses true experiment post test with cantrol group design. With 3 concentrations of infusa and the sample size was 625 samples in 5 repetitions. Result: The results of the study of red guava leaves infected the highest larval mortality at a concentration of 1.05% with 96% mortality of the larvae. The results showed that the difference of mortality rate at each concentration of guava leaf infusa was indicated by p value <0,05.Conclusion: Red guava leaf infusa infected infected was use with a concentration of 1.05% as the most effective concentration killed the larvae with 96.0% mortality percentage, but in general the concentration of red guava leaf infected concentration of 1.05% still can not kill the Aedes mosquito larvae 100% aegypti such as temephos.